The transition of brown regions: A matter of timing? - Stefano Basilico; Nils Grashof (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
Green innovations aim to improve and reduce the environmental impact of economic activities. Thus far, research focus on the positive trajectories of green transition. Recent studies focus also on the speed of transition and on its effects on economic outcomes. Continuing in this direction we focus on brown regions (i.e. specialized in fossil-fuel technologies) and the challenges that they face to become sustainable. Taking as example German Labour Market Regions we identify brown regions and measure their transition using an innovative approach based on Social Network Analysis and Knowledge Spaces. We find that the earlier a region transitioned to green technologies, the better it is for both its social and economic outcomes. Our findings imply that the transition of brown regions has effects on socio-economic outcomes not yet accounted for in the sustainability transition literature.
Keywords: O32; O33; R11; 330; green transition; green technologies; knowledge spaces; network embeddedness; socio-economic development